Kepatuhan Partai Politik Tentang Verifikasi Partai Politik Peserta Pemilu Tahun 2024 - Haikal, Muhamad; Rahmawati, Nurlalili (Legal Community Associations, 2024)
The principle of democracy or popular sovereignty can ensure the participation of the community in the decision-making process. In the concept of democracy, the position of the people is placed in a very strategic position in the constitutional system. The means of realizing democracy is in the process of general elections (PEMILU), through elections the realization of people's sovereignty is produced by representatives and state governments. This thesis aims to find out the mechanism of registration and verification of political parties and the legal application of the verification of political parties carried out by the General Election Commission based on PKPU number 4 of 2022. This research uses a qualitative research approach by seeking meaning, understanding, understanding, verstehen about a phenomenon, event, or human life by being directly or indirectly involved in the setting under study, contextual, and comprehensive. The results of this study indicate that there are several stages based on PKPU Number 4 of 2022, namely registration, administrative verification, factual verification and determination of political party participants in the 2024 elections. There are several findings in the field that become obstacles in the verification process such as the incompatibility of data provided by political party participants to the General Election Commission. Political party participants objected to the verification stage process. The process of stages applied by the KPU to general election participants in the form of registration, verification, and determination is in line with PKPU Number 4 of 2022 concerning Registration, Verification and Determination of Political Parties Participating in the Election of the House of Representatives and the Regional House of Representatives. Prinsip demokrasi atau kedaulatan rakyat dapat menjamin peranan serta masyarakat dalam proses pengambilan keputusan. Dalam konsep demokrasi posisi rakyat ditempatkan dalam posisi yang sangat strategis dalam sistem ketatanegaraan. Bentuk sarana perwujudan demokrasi ialah dalam proses pemilihan umum (PEMILU), melalui pemilu perwujudan kedaulatan rakyat dihasilkan wakil dan pemerintah negara. Tulisan ini bertujuan untuk mengetahui mekanisme pendaftaran dan verifikasi partai politik dan penerapan hukum dari adanya verifikasi terhadap partai politik yang dilakukan oleh Komisi Pemilihan Umum oleh komisi pemilihan umum berdasarkan PKPU nomor 4 tahun 2022. Penelitian ini menggunakan metode penelitian Pendekatan Penelitian kualitatif yakni dengan cara mencari makna, pemahaman, pengertian, verstehen tentang suatu fenomena, kejadian, maupun kehidupan manusia dengan terlibat langsung atau tidak langsung dalam setting yang diteliti, kontekstual, dan menyeluruh. Hasil penelitian ini menunjukkan bahwa terdapat beberapa tahapan berdasarkan PKPU Nomor 4 tahun 2022 yakni pendaftaran, verifikasi administrasi, verifikasi faktual dan penetapan peserta partai politik pada pemilu tahun 2024. Terdapat beberapa penemuan di lapangan yang menjadi kendala dalam proses verifikasi seperti tidak sesuainya data-data yang diberikan oleh peserta partai politik kepada Komisi Pemilihan Umum. Peserta partai politik merasa keberatan akan adanya proses tahapan verifikasi. Proses tahapan yang diberlakukan oleh KPU kepada peserta pemilihan umum yang berupa pendaftaran, verfikasi, dan penetapan sudah selaras dengan PKPU Nomor 4 Tahun 2022 tentang Pendaftaran, Verifikasi dan Penetapan Parpol Peserta Pemilu DPR dan DPRD.